The Journalism Agenda Guide (JAG): Proposal for Applied Research in Journalism (ARJ) - Guerra, Josenildo Luiz (Brazilian journalism research, 2016)
This article proposes the Journalism Agenda Guide (JAG), a technical tool for managing journalistic content. Developed from an Applied Research in Journalism (ARJ) methodology, the Guide is based on articulating concepts of Agenda Setting, Journalistic Relevance (JR), organizational productivity and Semantic Resolution (SR). The basis of the Guide is the relation between the relevance of a theme and how much space it should occupy in the news, subject to a particular organization’s production capacity. Incorporating the Guide as a tool for editorial management means adopting practices of accountability which affect both the ethical conduct an organization and its professionals adhere to and the sustainability of companies, becoming an important ally in the efforts to consolidate the credibility in journalism.